Traditional knowledge applied to the management of small tank wetland systems in Sri Lanka - Curnow, Jayne; de Silva, Sanjiv (Springer, 2016)
The foundation of rice production in the dry zone of Sri Lanka is a hydraulic civilization spanning at least 2,000 years, and based on constructed small irrigation tanks. Dotted across much of the dry zone, and often constituting cascades, the traditional management of these tanks for dry season irrigation water brought together sophisticated engineering skills, deep ecological knowledge and social organisation around the practical need for cooperation and spiritual belief systems. While these small tanks are often referred to with respect to their centrality to irrigating rice, the staple crop, the use of both natural and built elements in managing the tanks and their surrounding landscapes in fact constitute a remarkable multi-functional system that has provided a range of ecosystem services for human well-being. Despite its ancient roots, the ecological principles inherent in the traditional knowledge shaping this system resonate closely with modern concepts around natural resource management such as wise use, sustainability, social ecological systems and green infrastructure.